Once-weekly insulin icodec with dosing guide app versus once-daily basal insulin analogues in insulin-naive type 2 diabetes (ONWARDS 5) : A randomized trial - YAVUZ, DİLEK (My University, 2023)
Background: Inadequate dose titration and poor adherence to basal insulin can lead to suboptimal glycemic control in persons with type 2 diabetes (T2D). Once-weekly insulin icodec (icodec) is a basal insulin analogue that is in development and is aimed at reducing treatment burden. Objective: To compare the effectiveness and safety of icodec titrated with a dosing guide app (icodec with app) versus once-daily basal insulin analogues (OD analogues) dosed per standard practice. Design: 52-week, randomized, open-label, parallel-group, phase 3a trial with real-world elements. (ClinicalTrials.gov: NCT04760626) Setting: 176 sites in 7 countries. Participants: 1085 insulin-naive adults with T2D. Intervention: Icodec with app or OD analogue (insulin degludec, insulin glargine U100, or insulin glargine U300). Measurements: The primary outcome was change in glycated hemoglobin (HbA1c) level from baseline to week 52. Secondary outcomes included patient-reported outcomes (Treatment Related Impact Measure for Diabetes [TRIM-D] compliance domain score and change in Diabetes Treatment Satisfaction Questionnaire [DTSQ] total treatment satisfaction score). Results: The estimated mean change in HbA1c level from baseline to week 52 was greater with icodec with app than with OD analogues, with noninferiority (P < 0.001) and superiority (P = 0.009) confirmed in prespecified hierarchical testing (estimated treatment difference [ETD], −0.38 percentage points [95% CI, −0.66 to −0.09 percentage points]). At week 52, patient-reported outcomes were more favorable with icodec with app than with OD analogues (ETDs, 3.04 [CI, 1.28 to 4.81] for TRIM-D and 0.78 [CI, 0.10 to 1.47] for DTSQ). Rates of clinically significant or severe hypoglycemia were low and similar with both treatments. Limitation: Inability to differentiate the effects of icodec and the dosing guide app. Conclusion: Compared with OD analogues, icodec with app showed superior HbA1c reduction and improved treatment satisfaction and compliance with similarly low hypoglycemia rates.
Keywords: Adverse events; Clinical trials; Confidence intervals; HbA1c; Hypoglycemia; Hypoglycemics; Insulin; Randomized trials; Safety; Treatment guidelines